2005
DOI: 10.1152/jn.00281.2005
|View full text |Cite
|
Sign up to set email alerts
|

Activity-Independent Coregulation of IA and Ih in Rhythmically Active Neurons

Abstract: The fast transient potassium or A current (IA) plays an important role in determining the activity of central pattern generator neurons. We have previously shown that the shal K+ channel gene encodes IA in neurons of the pyloric network in the spiny lobster. To further study how IA shapes pyloric neuron and network activity, we microinjected RNA for a shal-GFP fusion protein into four identified pyloric neuron types. Neurons expressing shal-GFP had a constant increase in IA amplitude, regardless of cell type. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
170
0

Year Published

2007
2007
2022
2022

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 132 publications
(177 citation statements)
references
References 48 publications
7
170
0
Order By: Relevance
“…We showed that although the same identified neurons in different animals display 3-to 5-fold variability in the level of expression of any one ion channel, these expression levels are not independently variable, but show cell-specific correlations. Although compensatory changes in gene expression have been demonstrated previously between shal and IH (27,28), our work reveals the potential extent to which channel genes are coregulated in neurons known to maintain constant function in the networks in which they function (29). We argue that cell identity is not a static result of gene expression, but rather a continual balance between compensatory changes in gene expression and coordinated gene regulation that ensures robust output.…”
Section: Discussionmentioning
confidence: 62%
“…We showed that although the same identified neurons in different animals display 3-to 5-fold variability in the level of expression of any one ion channel, these expression levels are not independently variable, but show cell-specific correlations. Although compensatory changes in gene expression have been demonstrated previously between shal and IH (27,28), our work reveals the potential extent to which channel genes are coregulated in neurons known to maintain constant function in the networks in which they function (29). We argue that cell identity is not a static result of gene expression, but rather a continual balance between compensatory changes in gene expression and coordinated gene regulation that ensures robust output.…”
Section: Discussionmentioning
confidence: 62%
“…Consistent with this hypothesis, recent studies performed in the invertebrate nervous system have demonstrated that numerous ion channels/ currents display correlated levels of expression/amplitude in unperturbed populations of neurons (MacLean et al, 2005;Schulz et al, 2006Schulz et al, , 2007Khorkova and Golowasch, 2007;Goaillard et al, 2009;Tobin et al, 2009;Temporal et al, 2011). Moreover, some of these correlations in ion channel properties were demonstrated to be cell-type specific and strongly predict the functional output of the neuron (Schulz et al, 2007;).…”
Section: Introductionmentioning
confidence: 81%
“…Furthermore, activity-dependent changes in synapses and in VGICs underlying some functional maps have shown to be governed by the same underlying signaling mechanisms (3,(41)(42)(43)(44)(45), imposing additional dependencies on the covariance among these functional maps. Finally, there is experimental evidence from several systems for activity-dependent and independent mechanisms of maintaining the coexpression of specific conductances (13,15,(46)(47)(48)(49)(50)(51)(52)(53). How do we reconcile these observations with the absence of strong pairwise correlations (Fig.…”
Section: Discussionmentioning
confidence: 97%